2015
DOI: 10.1590/1980-57642015dn93000010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and engagement in physical, social and intellectual activities in older adults: The FIBRA study

Abstract: Cognitive decline in aging can negatively impact quality of life in the elderly. However, studies have shown that elderly engaged in advanced activities of daily living (AADLs) can maintain or enhance global cognitive function or specific domains.ObjectiveTo investigate the relationship between engagement in AADLs and domains of cognition in elderly from seven different locations in Brazil.MethodsA cross-sectional study involving 2,549 elderly without cognitive deficits suggestive of dementia was conducted. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 42 publications
0
32
0
9
Order By: Relevance
“…An alternative explanation lies in lack of interpersonal interactions and cognitive stimulation in prison. Some studies have shown an association between increased levels of engagement in social, physical or intellectual activities and higher cognitive ability scores in older people aged 65 years and above (Sposito et al, ), and some studies have shown that loneliness is a crucial marker of cognitive decline (Cacioppo and Hawkley, ). In their daily lives, older prison inmates make few choices, in that they do not plan their activities throughout the day, decide what to eat and they do not have to cope with administrative tasks.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation lies in lack of interpersonal interactions and cognitive stimulation in prison. Some studies have shown an association between increased levels of engagement in social, physical or intellectual activities and higher cognitive ability scores in older people aged 65 years and above (Sposito et al, ), and some studies have shown that loneliness is a crucial marker of cognitive decline (Cacioppo and Hawkley, ). In their daily lives, older prison inmates make few choices, in that they do not plan their activities throughout the day, decide what to eat and they do not have to cope with administrative tasks.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation lies in lack of interpersonal interactions and cognitive stimulation in prison. Some studies have shown an association between increased levels of engagement in social, physical or intellectual activities and higher cognitive ability scores in older people aged 65 years and above (Sposito et al, 2015), and some studies have shown that loneliness is a crucial marker of cognitive decline (Cacioppo and Hawkley, 2009). In their daily lives, older prison inmates make few choices, in that they do not plan their activities throughout the day, decide what to eat and they do not have to cope with administrative tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we distinguish physical, social, and intellectual activities, which is common in the cognitive aging literature (see e.g. Fratiglioni, Paillard-Borg, & Winblad, 2004;Lam et al, 2015;Sposito, Neri, Yassuda, 2015;Wang, Xu, & Pei, 2012). These separate categories have been found to predict outcomes in different ways (Lam et al, 2015;Wang, Xu, & Pei, 2012) and also highlight potential pathways for benefits: Social activities may provide social support, in particular in times of distress (Iso-Ahola & Park, 1996), and feelings of relatedness and belonging (Kuykendall et al, 2018).…”
Section: Changes In Leisure Activity After Retirementmentioning
confidence: 95%